2004
DOI: 10.1002/dvdy.20123
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia‐induced TGFβ and fibronectin expression in embryonic mouse heart

Abstract: Cardiovascular defects are common in diabetic offspring, but their etiology and pathogenesis are poorly understood. Extracellular matrix accumulates in adult tissues in response to hyperglycemia, and transforming growth factor-beta1 (TGF␤1) likely mediates this effect. The objective of this study was to characterize TGF␤ expression in the organogenesisstage mouse heart and to evaluate TGF␤ and fibronectin expression in embryonic mouse heart exposed to hyperglycemia. Prominent TGF␤1, and minimal TGF␤2 or TGF␤3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…We found that the total level of TGFβ ligands, especially TGFβ1 and TGFβ3, were reduced by maternal diabetes. This finding is consistent with what described by Zhao et al in E10.5 hearts 17 , but contradicts a previous in vitro study, which described a slight decrease in TGFβ1 expression in the mouse (E9.5) embryonic heart when exposed to high glucose for 24 hours 2 . This discrepancy may be explained by the different stages of hearts that were examined in the two studies.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We found that the total level of TGFβ ligands, especially TGFβ1 and TGFβ3, were reduced by maternal diabetes. This finding is consistent with what described by Zhao et al in E10.5 hearts 17 , but contradicts a previous in vitro study, which described a slight decrease in TGFβ1 expression in the mouse (E9.5) embryonic heart when exposed to high glucose for 24 hours 2 . This discrepancy may be explained by the different stages of hearts that were examined in the two studies.…”
Section: Resultssupporting
confidence: 90%
“…Major cardiac defects including persistent truncus arteriosus and ventricular septal defects (VSDs) are often seen in offspring of diabetic women 1, 2 . Because the number of women of reproductive age (18-44 years old) with diabetes is increasing 3 , diabetes-induced heart defects have become an urgent health problem 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because trehalose prevents alteration of gene expression that regulates autophagy, trehalose may activate autophagy by modulating gene expression. Previous studies have shown that JNK1/2 activation (23, 24), TGF␤ pathway disturbance (40), and diminished Wnt signaling (35) are critically involved in the induction of diabetic embryopathy. These three signaling pathways regulate the autophagy process (20,32,52).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to determine the direct hyperglycaemic effects on contractile functions and important intracellular signalling pathways in myocytes. The signalling molecules investigated in this study are restricted to those intracellular molecules found in the angiotensin II-induced pathway in adult ventricular cardiomocytes because there is some evidence that these molecules are also involved in the hyperglycaemic pathway [21,22,23].…”
Section: Introductionmentioning
confidence: 99%